2005
DOI: 10.1051/radiopro:2005s1-046
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic box model to predict the radionuclide behaviour in rivers for medium and long-term periods

Abstract: Abstract. This paper presents a dynamic box model for the radionuclide behaviour in rivers on medium-and long-term periods (several days to several years). The river is described as a succession of boxes representative of its different reaches. In each reach, the compartments are the water column and three bottom sediment layers. Called interface, the first layer plays a fundamental role for the vertical exchanges of solid radionuclide phases between the water column and the sediment. The second layer results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…[3] It has been shown that assessing the sediment flux could provide a basis for evaluating the eroded flux of pollutants [Boyer et al, 2005]. The erosion flux E (kg m À2 s À1 ) is quantified by threshold laws [Partheniades, 1965;Winterwerp and van Kesteren, 2004], which involve the ratio between the bed shear stress t (N m À2 ) of the flow and the critical erosion shear stress of the eroded surface t ce (N m À2 ).…”
Section: Introductionmentioning
confidence: 99%
“…[3] It has been shown that assessing the sediment flux could provide a basis for evaluating the eroded flux of pollutants [Boyer et al, 2005]. The erosion flux E (kg m À2 s À1 ) is quantified by threshold laws [Partheniades, 1965;Winterwerp and van Kesteren, 2004], which involve the ratio between the bed shear stress t (N m À2 ) of the flow and the critical erosion shear stress of the eroded surface t ce (N m À2 ).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, modelling was performed with the CASTEAUR code that evaluates, according to space and time, the radionuclide concentrations in the main abiotic and biotic compartments of a river (Boyer et al 2005;Duchesne et al 2003). For this study, three modules of the code were used: -The hydrographical module represents the geometry of the river as a succession of reaches, each described by its length, slope, roughness and trapezoidal section.…”
Section: Danio Rerio Maintenance and Egg Productionmentioning
confidence: 99%
“…The code Casteaur v0.1 (Boyer et al, 2005;Boyer and Beaugelin-Seiller, 2002;Beaugelin-Seiller et al, 2002;Duchesne et al, 2003) is dedicated to operational assessments of the radionuclides transfers in rivers. It is based on five modelling layers: a hydrographical model, a hydraulic model, a sedimentary model, a trophic chain model and a radioecological model.…”
mentioning
confidence: 99%